DAMPAK KECANDUAN PENGGUNAAN GADGET TERHADAP PERKEMBANGAN SOSIAL EMOSIONAL ANAK USIA 5-6 TAHUN (STUDI KASUS DI KELURAHAN GIRITIRTA, KECAMATAN PEJAWARAN, BANJARNEGARA) - Retno ‘Aina Rahayu; Desti Pujiati (Prosiding Temu Ilmiah Nasional Guru, 2024)
The background to this research is the increasing use of gadgets among children which raises concerns regarding its impact on social emotional development. This research aims to determine the impact of addiction to using gadgets on the social emotional development of children aged 5-6 years in Giritirta Village, Pejawaran District, Banjarnegara Regency. The method used is a case study with a qualitative approach. Data collection techniques used include observation, interviews and documentation of activities. The research results show that the use of gadgets has a significant impact on the social emotional development of young children, including causing emotional instability, dependence on gadgets, as well as decreasing interest in physical activity and reducing interactions with peers. Researchers recommend that parents limit the use of gadgets and carry out strict supervision when children play with gadgets so that they do not become addicted to gadgets.